A historical Analysis of Politics of Self Inscription and Struggle for National Identity among the BaTonga of middle Zambezi Valley, Binga in Zimbabwe in the 21st Century - Mwinde, Melusi (Midlands State University, 2018)
This research attempts to unearth the dynamics of the struggles of the BaTonga tribe of Binga in the quest for national identity. The research grapples with competing forces which hinders the minority groups in attainment of their autonomous identity without contradicting national question of identity formation project. What has emerged in post-colonial state is conflation of minority tribes into two major competing which are Shona and generalisation of identity of these groups. The research also attempts to trace the historical background of the marginalisation of the BaTonga tribe of Binga district from the pre displacement era of 1959.It also exposes the general attempt by the pre and post-colonial regime in denying the Tonga in regaining the attempt. As if that is not enough, the research also attempts to expose the strategies employed by the BaTonga in regaining their identity. The research also evaluates the impact of those attempts in regaining their autonomous identity in the 21st century